Towards Irrigation Modernisation in the Ogun-Oshun River Basin, Nigeria: Opportunities, Challenges, and Improvement Options - Adeboye, O. B.; Oyedele, D. J.; Tanimonure, V. A.; Opayinka, A. O.; Aduwo, O. E.; Olusegun, A. T.; Yusuf, A. A.; Oyewole, L. A.; Odunaiya, O. O.; Chukalla, A. D.; Adugna, E. B.; Solomon, T. T.; et al. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2026)
Irrigated agriculture is very crucial in achieving the Sustainable Development Goal (SDG) and ensuring food security in Nigeria. The study examines the opportunities and the challenges of the selected thirteen Irrigation Farm Projects in the Ogun Oshun River Basin Authority (OORBA). Data were obtained by interviews from the stakeholders in the management of the irrigation schemes. The study reveals that land areas range from 150 ha for the Lower Ogun Irrigation Project in Mokoloki to 3,500 ha for the Middle Ogun Irrigation Project in Iseyin. However, the level of utilisation of the land resources varies from 6.2% to 100%. Interestingly, it was observed that a good correlation between the irrigable land area and the area actually irrigated (r2 = 0.7982), and the irrigable areas and the actual irrigated areas under large Irrigation Farm Projects (r2 = 0.70) exist, unlike the small Irrigation Farm Projects (r2 = 0.09). Therefore, it indicates that the smallholder farmers in the large Irrigation Farm Projects utilised the land resources better. However, where underutilisation was pronounced, it is due to ageing irrigation and energy infrastructure, poor access roads and networks, and inadequate modern farm machinery. Surface water resources are abundant in the selected Irrigation Farm Projects, which, if well explored, could transform the irrigated agriculture in the basin and reposition OORBD as the food basket for the Southwest, Nigeria and the neighbouring African countries. The poor performance of the public Irrigation Farm Projects in the OORBD is due to low financial investment in the projects, poor economic conditions, lack of weather early warning systems and networks to mitigate the effects of climate change. Opportunities for transforming irrigated agriculture in the basin are the application of sensors in irrigation water management and drones for smart agriculture, renewable energy, micro-irrigation systems, access roads and market, regular training of farm managers and the early warning systems networks.